Rationalized and Extended Democracy Inserting Public Scientists into the Legislative/Executive Framework, Reinforcing Citizens' Participation - Molteni Tagliabue, Giovanni (Studi e saggi, 2023)
In this book, Giovanni Molteni Tagliabue asserts that the realization of the values and the implementation of the objectives as indicated in democratic constitutions (political, social rights and the people's welfare) are hindered by structural defects of the legislative/government architecture and processes. Expertise and science have scarce say in politics and policy. The author suggests an innovative view through the 'REDemo Project'. 1. Rationalization: the insertion of public scientists into legislative/executive mechanisms, with the creation in each democracy of a National Scientific Assembly - parallel to the extant partypolitical Chamber of Representatives - consisting of academic experts and researchers (legal scholars, political analysts, economists, sociologists, land/urban planners, industry/infrastructure designers, biotechnologists, agronomists, ecologists, educationists, specialists on public health, on cultural heritage, etc.) elected by universal suffrage; 2. Extension: the broadening of the institutions of direct democracy and reinforcement of the electorate as decision-maker of last resort. So the main themes and objectives of the book are an examination of the major flaws in today's democracies (pars destruens) and a proposal for a renewed institutional framework (pars construens).